2022
DOI: 10.3390/antibiotics11101433
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID-19 Pandemic on Outpatient Antibiotic Prescription Rates in Children and Adolescents—A Claims-Based Study in Germany

Abstract: The aim of the study was to examine whether the COVID-19 pandemic had any effect on antibiotic prescription rates in children in Germany. Using the nationwide outpatient prescription data from the Statutory Health Insurance from 2010 to 2021, changes in the monthly prescriptions of systemic antibiotics dispensed to children aged 0–14 years were examined (n = 9,688,483 in 2021). Interrupted time series analysis was used to assess the effect of mitigation measures against SARS-COV-2, introduced in March and Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, the trend observed during the first year of the pandemic (2020) was obvious in both sexes. Furthermore, in accordance with the findings of previous analyses, fracture incidence rates detected in the second year of the pandemic duplicated values observed in 2020 across all age groups investigated [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…However, the trend observed during the first year of the pandemic (2020) was obvious in both sexes. Furthermore, in accordance with the findings of previous analyses, fracture incidence rates detected in the second year of the pandemic duplicated values observed in 2020 across all age groups investigated [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the decline observed from 2020 to 2021 (−11.3%) remains within the range of the decreases observed prior to the pandemic, which supports the hypothesis of a collapse in AB prescriptions from 2019 to 2020 and a normalization a year later at a level comparable to the pre-pandemic level. Akmatov and colleagues also observed this effect when they investigated the development of AB prescriptions in children, identifying a dramatic decline from 2019 to 2020 with a slight increase in 2021 [22]. However, regardless of the extent to which the pre-pandemic development and the decline in the incidence of infectious diseases might have influenced the profound reduction in AB prescriptions in 2020, there are a number of other factors that could be responsible for the development observed.…”
Section: Discussionmentioning
confidence: 92%
“…In a study investigating the use of antibiotics during the COVID-19 pandemic in hospitals in China compared to previous rates, a remarkable decrease was noted [21]. In this context, Akmatov and colleagues investigated prescriptions for antibiotics in children (≤14 years) in Germany, detecting an annual decrease of 6% prior to the pandemic, with the figure halving (57%) in 2021 in comparison to the level in 2019 [22].…”
Section: Introductionmentioning
confidence: 99%
“…The decreasing trend in antibiotic prescribing in recent years may also be related to the coronavirus disease 2019 (COVID-19) pandemic. As a matter of fact, a claims-based study of children and adolescents in Germany (N = 9,688,483 participants in 2021) found that the decrease in outpatient antibiotic prescriptions was more pronounced for some months in 2020 compared to prior years, although this effect was temporary [37]. This decrease following the outbreak of the pandemic may have been related to lower access to medical care and partial drug shortages in community pharmacies.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%